Implementation of the Singing Method to Improve the Numeracy Skills of Grade 1 Immigrant Children in Malaysia - Prisma Anggi Armadila , Viola; Laksana, Sigit Dwi; Saputro , Anip Dwi (IJCER (International Journal of Chemistry Education Research), 2026)
This study aims to examine the singing method as a learning strategy to improve the numeracy skills of grade 1 students at SB AMI Penang, Malaysia. This research uses a qualitative method with a case study approach whose data is collected through observation, in-depth interviews, and documentation. This study involved 11 participants, consisting of 8 students in class 1A and 3 students in class 1B conducted at the Sanggar Bimbingan AMI in Penang, Malaysia, a non-formal educational institution that provides learning services for primary school children. The results of the study show that the singing method is able to create a pleasant learning atmosphere, increase student activity, and help students remember the sequence of numbers and understand simple summation through lyrics, rhythm, and hand movements. The singing method is more optimal if there is help from other learning media. The contribution of this research focuses on the development of innovative learning methods in a non-formal educational environment, especially in improving basic mathematics skills. The findings show that this method is effective as an alternative to numeracy learning in non-formal education with limited resources.